Activation of jird (Meriones unguiculatus) macrophages by the filarial parasite Brugia pahangi. - Jeffers, G W (1984)
Peritoneal macrophages from Mongolian jirds (Meriones unguiculatus) with either lymphatic or intraperitoneal infections of Brugia pahangi were studied to determine the effects of infection on macrophage function and morphology. Macrophages were collected at 40, 90, 140, and 200 days after inoculation of infective third-stage larvae and assayed for phagocytic and bactericidal activity by the acridine orange method and for morphological changes by light and electron microscopy. Significant increases in phagocytic and microbicidal activity (P less than or equal to 0.01) were observed in peritoneal macrophages collected from jirds with intraperitoneal infections when compared with peritoneal macrophages from jirds with lymphatic infections and resident peritoneal macrophages from normal, noninfected jirds. Morphological changes in peritoneal macrophages from jirds with intraperitoneal infections were similar to those found in thioglycolate-elicited macrophage populations. Granuloma formation was also observed in the peritoneal cavities of intraperitoneally infected jirds. The peritoneal cavity may serve as a model to study cell-worm interactions in filarial nematode infections.